PENGARUH PERAN TENAGA PERSONAL SELLING TERHADAP KEPUTUSAN MENJADI NASABAH PADA PT. ASURANSI CENTRAL ASIA (ACA) CABANG JAMBI - Akhmad Irwansyah Siregar; Ahmad Tarmizi; Lia Andini (J-MAS (Jurnal Manajemen dan Sains), 2017)
One strategy to win intense competition is by having the personal selling competent and professional. Personal selling is one of strategy of marketing for communicating information about products and services directly to the consumer ( face to face). Research objectives: 1) to know the influence role agent personal selling decision to Customers At PT. Asuransi Central Asia (ACA) Branch Jambi. .2) to know bigger the influence role agent personal selling decision to Customers At PT. Asuransi Central Asia (ACA) Branch Jambi. The data be used data primary data by questioner to 94 respondents. The method of analysis the data used linear regression simple. The results of the study based on the t value personal selling of -2,265 and t table of 1,622 from the comparison thitung = -2,265 smaller than ttabel = 1,622, H0 received Ha rejected it means agent personal selling not significant decision to Customers At PT. Asuransi Central Asia (ACA) Branch Jambi. The size of influence agent personal selling described by variable take the decision at  PT. Asuransi Central Asia (ACA) Branch Jambi of 5.3 percent. While the rest 94,7 percent influenced or described by other factors. Large relation between variables agent personal selling with the decision take the calculated with the correlation coefficient is 0,230 showed relationships low .Keyword : personal selling, insurance